2011
DOI: 10.1007/s00784-010-0502-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gluma Desensitizer on the tensile strength of zirconia crowns bonded to dentin: an in vitro study

Abstract: This study tested the impact of Gluma Desensitizer on the tensile strength of zirconia crowns bonded to dentin. Human teeth were prepared and randomly divided into six groups (N = 144, n = 24 per group). For each tooth, a zirconia crown was manufactured. The zirconia crowns were cemented with: (1) Panavia21 (PAN), (2) Panavia21 combined with Gluma Desensitizer (PAN-G), (3) RelyX Unicem (RXU), (4) RelyX Unicem combined with Gluma Desensitizer (RXU-G), (5) G-Cem (GCM) and (6) GCem combined with Gluma Desensitize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 28 publications
3
40
1
Order By: Relevance
“…Additionally, Sailer et al28 showed statistically increased shear bond strength values when glutaraldehyde/HEMA containing desensitizer was applied before self-adhesive cement luting. Moreover, Stawarczyk et al23 showed increased shear bond strength values even after aging procedures and also it has been revealed that Gluma had a positive effect on the tensile bond strength of self adhesive resin cements even with chewing simulations 30. These results are in agreement with the findings of the current study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, Sailer et al28 showed statistically increased shear bond strength values when glutaraldehyde/HEMA containing desensitizer was applied before self-adhesive cement luting. Moreover, Stawarczyk et al23 showed increased shear bond strength values even after aging procedures and also it has been revealed that Gluma had a positive effect on the tensile bond strength of self adhesive resin cements even with chewing simulations 30. These results are in agreement with the findings of the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Hitz18 et al showed the negative impact of thermocycling on bond strength of dentin and self-adhesive resin cement interface. Contrary to these findings, Sailer et al28 showed predominantly cohesive failure despite the absence of the thermocycling process; indicating the cement itself was the weakest link and Stawarczyk et al30 also showed cohesive failure before and after aging procedures.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The size of the specimen (n=12 per subgroup) was based on a previous study, which showed significant differences with a similar specimen size. 13 No formal power analysis was performed prior to initiation of the study. The cements were occlusal photopolymerized for 30 s (Elipar S10, 3M ESPE).…”
Section: Methodsmentioning
confidence: 99%
“…However, the teeth were prepared manually, and the water supply was not controlled with the handpiece as under clinical conditions. In a previous study, where the tensile strength of zirconia crowns cemented with selfadhesive resin cements on dentin were tested, 13 the results ranged between 7.3 MPa and 14.1…”
mentioning
confidence: 99%